Morphological characteristics of Portuguese rhythmic gymnasts in different competition levels - Batista, A.; Garganta, R.; Avila-Carvalho, L (Collegium Antropologicum, 2019)
This study aimed to: (1) compare morphological and training characteristics in Portuguese gymnasts across competi?tive levels; (2) investigate the morphological variables with higher discriminatory power between groups; (3) determine which morphological variables better explain performance. The sample (n=164) consisted of gymnasts at three competition levels (base, 1st division and elite) from Portugal. 19 anthropometric and 2 body composition measurements were performed. Somatotype was defined by Health-Carter method. Training data were collected by interviewing. For the statistical analyses, Kruskal-Wallis test, linear regression and discriminant function were used. Portuguese gymnasts (13.5±2.0 years) presented 43.7±9.3 kg of body mass, 152.6±8.9cm of height, 18.5±2.4k g/m2 of BMI, 17.5±4.1% of body fat, endomorph-ectomorph somatotype and 16.9±7.5 hours/week of training volume. Elite gymnasts differed from other groups in having lower skinfolds and body fat; and higher training volume and training years. The elite and the 1st division showed higher ectomorphy and lower endomorphy component than the base. Thus, the elite presented morphological and training characteristics closer to the international standards, followed by the 1st division and the base. The variables that best discriminate the gymnasts by competition levels were body fat and lower limb length. Furthermore, body fat was the main morphological predictor of performance in competition